2015
DOI: 10.1103/physrevd.91.063505
|View full text |Cite
|
Sign up to set email alerts
|

Irruption of massive particle species during inflation

Abstract: All species of (non-conformally-coupled) particles are produced during inflation so long as their mass M is not too much larger than H, the expansion rate during inflation. It has been shown that if a particle species that is normally massive (M H) couples to the inflaton field in such a way that its mass vanishes, or at least becomes small (M < H), for a particular value of the inflaton field, then not only are such particles produced, but an irruption of that particle species can occur during inflation. In t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 44 publications
(156 reference statements)
0
43
0
Order By: Relevance
“…We note xxxix In general this is not a consistent assumption to make if the background trajectory is turning in field space [97], however given (83), it can be shown that this is a consistent assumption to make even at the level of the effective action [80]. that in our derivation, the ψ quanta do not need to become exactly massless xl at φ * , as has typically been considered in the literature, only that the scale µ be such that the adiabatic condition (82) be violated, which can happen for reasonable values consistent with slow roll and the existence of the appropriate hierarchies between the mass of the heavy quanta and H. Of course, particle production is parametrically enhanced when the ψ quanta become exactly massless, as considered in [143][144][145][146][147][148], whose results can be viewed as a particular case of the treatment elaborated upon here.…”
Section: Light Particle Content and Particle Productionmentioning
confidence: 96%
“…We note xxxix In general this is not a consistent assumption to make if the background trajectory is turning in field space [97], however given (83), it can be shown that this is a consistent assumption to make even at the level of the effective action [80]. that in our derivation, the ψ quanta do not need to become exactly massless xl at φ * , as has typically been considered in the literature, only that the scale µ be such that the adiabatic condition (82) be violated, which can happen for reasonable values consistent with slow roll and the existence of the appropriate hierarchies between the mass of the heavy quanta and H. Of course, particle production is parametrically enhanced when the ψ quanta become exactly massless, as considered in [143][144][145][146][147][148], whose results can be viewed as a particular case of the treatment elaborated upon here.…”
Section: Light Particle Content and Particle Productionmentioning
confidence: 96%
“…The Superheavy Dark Matter (SHDM) φ, based on the possibility of particle production due to time varying gravitational fields, is an alternative DM scenario [19][20][21][22][23][24][25][26][27][28][29]. This scenario is based on three hypotheses: (a) SHDM in the early Universe never reaches LTE; (b) SHDM has a mass with the same order of magnitude as the inflaton mass; (c) the lifetime of SHDM exceeds the age of the Universe, that is τ φ ≫ t 0 [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the idea was originally introduced 7 as a means for reheating after inflation. Since 5 subsequent work [8][9][10][11] has elaborated on the basic scheme into a model with coupling between two scalar fields.…”
Section: Resonant Particle Production During Inflationmentioning
confidence: 99%